ChemInform Abstract: Mechanistic Insight to the Reaction Pathway of Aerobic Oxidative C—C Bond Cleavage of α‐Hydroxy Ketones. Issue 35 (8th August 2013) - Lui, Hui; Jiang, Xuefeng
Abstract Review: [70 refs.]